'A gift from God': autochthonous grapes and wine heritage on the island of Hvar, Croatia. (2nd October 2019) - Skinner, William
ABSTRACT: Wine is an integral part of life on the Croatian island of Hvar. Its significance is multivalent, from the importance of home production and consumption to its functions as a trade commodity and symbol of community and identity. Much of Hvar's wine grapes are grown in the Stari Grad Plain, a UNESCO World Heritage-listed cultural landscape. Economic factors mean grape and wine production can be a precarious pursuit, and although wine retains a central cultural position many farmers on the Plain are abandoning agriculture in favour of tourism industries. To increase value of their product, grape and wine producers seek to tap into discourses of 'heritage' that are understood locally and shaped by globalised discourses of authenticity and quality. Wine producers have identified autochthonous grape varieties, particularly bogdanuša, as important elements in the promotion of Hvar wine. These grapes are able to simultaneously access multiple registers of value due to their uniqueness, perceived quality, heritage significance, emplaced 'belonging' on the island, and relationship to cultural practices and other important elements of cultural patrimony, and producers are optimistic about their role in the future success of the wine industry on Hvar.